Review of the Lathrobium tahirai species group (Coleoptera: Staphylinidae: Paederinae) from Japan, with descriptions of six new species - Sato, Yuya; Maruyama, Munetoshi (Zootaxa, 2026)
The Lathrobium tahirai species group is reviewed and redefined based on detailed morphological examination of the type specimens and newly available materials from Japan. Six previously described species are redescribed and illustrated with additional taxonomically important characters: L. tahirai Y. Watanabe, 2001, L. kanayamaense Y. Watanabe, 2001, L. nikkoense Y. Watanabe, 2001, L. sinense Herman, 2003, L. krilioni Tikhomirova, 1976, and L. riozoi (Y. Watanabe, 1972) comb. nov. Moreover, L. inflatum Assing. 2013 syn. nov. is placed in synonymy with L. nikkoense. In addition, six new species of this species group from Japan are described and illustrated: L. koseii sp. nov. (Kyushu: Nagasaki Prefecture: Tsushima Is.), L. yatsugatakense sp. nov. (Honshu: Nagano Prefecture), L. hashizumeorum sp. nov. (Honshu: Nagano Prefecture), L. undulatum sp. nov. (Honshu: Nagano Prefecture), L. kainum sp. nov. (Honshu: Yamanashi Prefecture), and L. stomachiforme sp. nov. (Honshu: Yamanashi Prefecture). A key to species of the L. tahirai group is provided.